Implementasi Kegiatan Camping dalam Menumbuhkan Kemandirian Anak di TK Kuncup Melati Desa Sukolilo Kecamatan Sukodadi Kabupaten Lamongan - Zahrok, Fatimatuz (AJER: Advanced Journal of Education and Religion, 2025)
This study aims to describe the implementation of camping activities in fostering children’s independence at TK Kuncup Melati. The background of this research is the tendency of early childhood children to still rely on parents and teachers in fulfilling their daily needs. Independence is an essential aspect of development in early childhood, enabling children to take care of themselves, manage personal belongings, make simple decisions, and socialize with their environment.This research uses a qualitative approach with a case study method. The subjects of the study consisted of TK Kuncup Melati students, classroom teachers, and several parents. Data collection techniques included observation, interviews, and documentation.The results of the study show that camping activities provide direct experiences for children to practice independence through activities such as eating by themselves, maintaining personal hygiene, taking care of their belongings, and sharing responsibilities with peers. These findings align with Hurlock’s theory, which emphasizes that children’s independence develops through practice, habituation, and direct experience, as well as Erikson’s theory, which states that children aged 3–6 years are in the stage of initiative vs. guilt, where they learn to take initiative and build social relationships.The conclusion of this study is that camping activities can serve as an effective means to foster independence in early childhood.